The rivals [large type] - Pek, Jane (Thorndike Press, a part of Gale, a Cengage Company, 2025)
"Claudia Lin has scored her dream job: co-running Veracity, a dating detective agency for New Yorkers who want to know if their prospective partners are telling the truth. Along the way, she and her colleagues--tech savant Squirrel, and the elegant and intimidating Becks--have uncovered a far-reaching AI conspiracy. And the corporate matchmakers may be resorting to murder to protect their secrets. In the wake of a client's sudden death, Claudia also fears that her brother is unwittingly being drawn into the matchmakers' deadly web. And as Becks reminds Claudia: spy tropes dictate that someone you trust will betray you"--